Ultra-transparent β-Ga2O3:Cr3+ glass-ceramics enabling high-efficiency true-transmission near-infrared light-emitting diodes - Shaoan Zhang; Yi Long; Penghui Zhang; Zaijin Fang; Zhenzhang Li; Huacong Ye; Guojun Zheng; Hong Jia; Jianrong Qiu; Yang Li (Journal of Advanced Ceramics, 2025)
Near-infrared phosphor-converted light-emitting diodes (NIR pc-LEDs), one of the most promising NIR light sources, have garnered significant attention owing to their compact structure, long lifetime and energy conservation. Despite these advantages, commercial NIR pc-LEDs employing pseudotransmission configurations, where the NIR phosphor and silicone composites are directly coated on blue LED chips, suffer from critical limitations in thermal management that severely deteriorate their NIR output performance. To address these intrinsic limitations, we developed an oxygen-coordination-competitive crystallization strategy to engineer high-transparency β-Ga2O3:Cr3+ glass-ceramics (GC). This strategy leveraged the strong oxygen affinity of Ga3+ ions, which drove the directional migration and recombination of Ga3+ and O2- ions within the isolated [GaO4] tetrahedral network during thermal processing. This controlled phase evolution enabled localized crystallization of the β-Ga2O3:Cr3+ nanocrystals while maintaining high transparency. The optimized β-Ga2O3:Cr3+ GC (0.4 mm thickness) achieved remarkable 81.2% NIR transmittance, approaching internal quantum efficiency (IQE ≈ 100%) and high thermal stability (89%@423 K). When this high-transparency β-Ga2O3:Cr3+ GC was employed as the NIR conversion material, the NIR GC-converted LEDs (GCc-LEDs) achieved 568 mW of NIR output power at a 500 mA drive current with a photoelectric conversion efficiency of 13%. The demonstrated performance metrics of NIR GCc-LEDs positioned this technology as an ideal NIR illumination source for next-generation point-of-care diagnostics, intelligent night vision systems, and nondestructive testing applications.